2007
DOI: 10.1089/vim.2007.0050
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to Dengue 1 Detected More Than 60 Years after Infection

Abstract: We investigated the duration of humoral responses to dengue virus infection in individuals who recalled experiencing dengue fever-like illnesses at the time of the Second World War, when dengue fever epidemics occurred throughout the Pacific and Southeast Asia. In July 1943 dengue fever reappeared in Hawaii following an interval of 31 years. Over the next 12 months a total of 1498 locally transmitted cases were reported, and at least 46 imported cases were identified, most of which were among members of the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 13 publications
2
68
0
Order By: Relevance
“…In contrast, inhibition of theh uptake of heterologous serotypes by the early convalescent sera from patients with primary DENV infection was observed only at low serum dilutions. This process may be the reason why a person can be transiently immune to the remaining three serotypes of DENV following an acute primary DENV infection (41,42). Further studies, however, would be needed to establish this notion.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, inhibition of theh uptake of heterologous serotypes by the early convalescent sera from patients with primary DENV infection was observed only at low serum dilutions. This process may be the reason why a person can be transiently immune to the remaining three serotypes of DENV following an acute primary DENV infection (41,42). Further studies, however, would be needed to establish this notion.…”
Section: Discussionmentioning
confidence: 99%
“…We found that CPI was highly effective against both DENV1 and DENV2 replication in cell cultures without obvious cytotoxicity. Together with other viruses, DENV infection usually induces generation of neutralizing antibodies, which protect the individuals from viral infection and even provide life-long protection against the homologous serotype (Imrie et al, 2007). Unfortunately, in a secondary infection by a different DENV serotype, the antibody from the previous infection could cross-react with the virus to form a non-neutralizing complex and result in enhancement of viral infection through a mechanism known as antibody-depen-dent enhancement (Halstead, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A primary DENV infection provides lifelong protection against disease caused by the infecting homologous serotype in most subjects (6). A secondary infection with virus of a heterologous serotype increases the risk of developing severe dengue hemorrhagic fever (7).…”
Section: Importancementioning
confidence: 99%